النظام الانضباطي ودوره في مكافحة الفساد الإداري في العراق - جزاع، إسراء طه (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
The aim of this study is to discuss the disciplinary system and its function in fighting administrative corruption in Iraq, where administrative corruption is damaging and threating administrative organizations. Iraq is placed at the bottom level (highly corrupt) in corruption perception index in the reports of transparent international organization during the last 15 years. This study discusses the legal ways and judicial and non-judicial means that help in addressing administrative corruption by identifying the specialized system to fight administrative corruption in Iraq. That system includes judicial, legislative and executive bodies. In addition, other parties that play direct and indirect role within the work of that system are also studied. Iraq has adopted the modern administrative judiciary method in relating to the employment system in general and the disciplinary system in particular. Therefore, the researcher has conducted the necessary comparison for each part of this research with those regulations in order to identify the agreement and disagreement. Moreover, the study investigates the association between implementing anti-corruption and sustaining the principle of separation of powers which prohibits the interference in the judicial authority and emphasizes on the complete independence of the judicial body. This study used the critical, comparative, and analytical descriptive approaches in order to identify the significance of the disciplinary system tools in fighting the phenomenon of administrative corruption. The results of the study show that the articles associated with corruption in the Iraqi law are not enough to control and fight the administrative corruption because there are some legal gaps within the text of these articles. These gaps must entirely be addressed to enforce the law properly and achieve the desired aims of an anti-corruption system. Thus, the researcher recommends making amendments to the current articles and adding new laws to fight and control administrative corruption. This study concludes that the relationship between the disciplinary system tools and administrative corruption is inverse and strong, where implementing more tools effectively to fight administrative corruption will contribute to lower the rates of administrative corruption in Iraq within administrative organizations.